Local Structural Investigation of (Ba,Ca)(Zr,Ti)O3 and Ca(Zr,Ti)O3 by X-Ray Fluorescence Holography - Yamamoto, Yuta; Kimura, Koji; Gadelmawla, Ahmed; Kawamura, Keisuke; Sugimoto, Hina; Liu, Donglin; Li, Qiang; Yan, Qingfeng; Khansur, Neamul Hayet; Happo, Naohisa; Kakimoto, Ken-Ichi; Webber, Kyle Grant; et al. (physica status solidi (b), 2022)
Analyses of the local structures around Zr doped in ferroelectric (Ba,Ca)(Zr,Ti)O3 (BCZT) and paraelectric Ca(Zr,Ti)O3 (CZT) are carried out by X-ray fluorescence holography. The images of the cations at the A and B sites of these ABO3 perovskites are clearly reconstructed from the measured holograms. In the real space images, a 0.2 Å outward displacement of the nearest Ba and Ca is observed in the atomic images of both BCZT and CZT, attributable to the difference in the ionic radius between Zr4+ and Ti4+. In addition, the first-neighboring Ti in BCZT is displaced inward by 0.5 Å, whereas no such displacement is observed in CZT. This shift of Ti in BCZT appears due to the large strain of the local lattice, and it can affect to the piezoelectric response of BCZT.
CRIS-Team Scopus Importer:2022-04-15
Keywords: ferroelectric materials; piezoelectric materials; X-ray fluorescence holography